Growth and Convergence in a Two-Region Model of Unified Germany - Michael Funke; Holge Strulik (Center for Economic Studies and ifo Institute (CESifo), 1999)
The paper sets up a two-region endogenous growth model to discuss growth and regional convergence of unified Germany. It emphasises the role of private and public capital accumulati on during the developing process. The theoretical part derives fiscal policy rules which establish convergence of regional output per capita and convergence of reginal human wealth. To assess the speed of convergence the model is calibrated with German da ta. Given a fiscal policy rule that is consistent with the data on government spending in East and West Germany after unification the model suggests that East Germany will reach eighty percent of West Germany's income per capita between 20 and 30 years after unification and that actual transfers are approximately sufficient to equalise regional human wealth. The results are compared with an extension of the model that includes wage setting behaviour and unemployment in the eastern region.
Keywords: 330; German unification; regional convergence; government spending